Способ прогнозирования изностойкости твердосплавных режущих инструментов - Нестеренко В. П. Владимир Петрович; Сериков Л. В. Леонид Вениаминович; Меркулов В. И. Валерий Иванович; Хоружий В. Д. Владимир Дмитриевич; Арефьев К. П. Константин Петрович; Тюрин Ю. И. Юрий Иванович
опубл. 27.03.05